PREDICTION OF ANTI-ALZHEIMER’S ACTIVITY OF FLAVONOIDS TARGETING CD33 THROUGH IN-SILICO APPROACH - S., AKILA; S., MALAR VIZHI; P., VIJAYALAKSHMI; A., CLARA MARY; M., RAJALAKSHMI (International Journal of Current Pharmaceutical Research, 2021)
Objective: Alzheimer's disease (AD) is a progressive, fatal brain disorder that would be putting a growing strain on health and social care systems. Present anti-AD agents are limited in their application due to their adverse effects, toxicity, and limited targets in AD pathology. As a result, it is important to develop an AD-fighting compound. Some flavonoids (such as kaempferol, myricetin, quercetin, and syringetin) have been shown to be effective in the treatment of Alzheimer's disease. Methods: We chose 284 flavonoids from the NPACT database for molecular docking studies in order to examine their binding interactions with the Alzheimer target protein CD33. Results: These compounds exhibited significant docking interactions with a variety of targets implicated in the pathogenesis of AD. We chose the top three compounds (Rutin, Morin, and,4,4'-Trihydroxydihydrochalcone) based on the scoring parameter. Conclusion: These compounds exhibited favorable pharmacokinetic properties, indicating that they could be attractive drug candidates for the treatment of Alzheimer's disease.